Development of a Practice-Based PKG PJOK Module to Improve Elementary School Teacher Competence - Anas Ardiansyah; Putri Febrianti; Anwar Anwar; Salahudin Salahudin; Rabwan Satriawan; Ainun Fitriani; Arif Mappatanga (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
The limited availability of practice-based professional development materials has hindered efforts to improve the competence of elementary school Physical Education, Sports, and Health (PJOK) teachers. This study aimed to develop a practice-based PKG PJOK module and evaluate its validity, practicality, and effectiveness. A Research and Development design using the ADDIE model was employed. Participants included material, media, and instructional design experts, as well as elementary school PJOK teachers involved in field testing. Data were collected through validation sheets, questionnaires, observations, and competency assessment instruments, then analyzed using descriptive quantitative and qualitative techniques. The findings indicated that the module was highly valid, practical, and effective in improving teachers' pedagogical and professional competence. The study concludes that the developed module is a feasible professional development resource and provides an evidence-based learning model to strengthen teacher competence in elementary physical education